2018
DOI: 10.1016/j.eururo.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Procedure-specific Risks of Thrombosis and Bleeding in Urological Non-cancer Surgery: Systematic Review and Meta-analysis

Abstract: The best evidence suggests that the benefits of blood-thinning drugs to prevent clots after surgery outweigh the risks of bleeding in some procedures (such as kidney transplantation procedures in patients at high risk of clots) but not others (such as prostate surgery in patients at low risk of clots).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 17 publications
0
58
0
1
Order By: Relevance
“…In the 1990s, when anticoagulation treatment for inpatients was not mature, some studies showed the incidence of VTE was in the range of 10-30% for hospitalized patients and interestingly the non-surgical inpatients suffering more deaths than surgical inpatients [9,10]. Recently, our previous research and other literatures have demonstrated that VTE event is not rare in non-oncological urology which can be associated with signi cant higher rate of intensive care hospital transfer, longer inpatient recover, more medical costs, and more mortality [6,11]. So early diagnosis of VTE can prevent a lot of troubles for human and sociaty because VTE is a preventable disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1990s, when anticoagulation treatment for inpatients was not mature, some studies showed the incidence of VTE was in the range of 10-30% for hospitalized patients and interestingly the non-surgical inpatients suffering more deaths than surgical inpatients [9,10]. Recently, our previous research and other literatures have demonstrated that VTE event is not rare in non-oncological urology which can be associated with signi cant higher rate of intensive care hospital transfer, longer inpatient recover, more medical costs, and more mortality [6,11]. So early diagnosis of VTE can prevent a lot of troubles for human and sociaty because VTE is a preventable disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is not enough high-quality evidence, the incidence of VTE in non-tumor surgery in urology is not as low as we think. For the major urological surgeries, the incidence of VTE varies from 0.3-10.8%, especially high in open recipient nephrectomy and open simple prostatectomy whose incidence is 1.3-5.3% and 2.7-10.8%, respectively [6]. Therefore, more attention should be paid to non-oncological patients in surgical departments.…”
mentioning
confidence: 99%
“…Guidelines are available to facilitate evidence-based use of thromboprophylaxis after surgery. 8,9 In 2012, the American College of Chest Physicians published a landmark article on thromboprophylaxis after non-orthopedic surgery. 8 This guideline suggested thromboprophylaxis use should be based on risk stratification using the Caprini score.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, thromboprophylaxis guidelines in urology have been published that are procedure specific and provide recommendations based on the procedure type and patient risk factors. 9 For this study, we hypothesized that all abdominopelvic procedures frequently performed for cancer would be associated with VTE risk, independent of Caprini score.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the American College of Chest Physicians (ACCP) published landmark guidelines on venous thromboprophylaxis following non-orthopedic operations (5). This publication was the best recognized guide for VTE prophylaxis following abdominal and pelvic surgery (including urological surgery) prior to the recently published European Association of Urology (EAU) procedure-specific guidelines (6). It is plausible that some of the improvements in VTE rates observed in this study are attributable to a change in practice patterns and the uptake of extended duration thromboprophylaxis following this publication.…”
mentioning
confidence: 99%